The Role of Agricultural Technology Development in Increasing Rice Farming Income in Banua Baru Village, Wonomulyo District - Ismawati; Dambe, Jumriani; Arfah, Salmawati (Tarjih : Agribusiness Development Journal, 2025)
The development of agricultural technology plays an essential role in increasing rice farming productivity and income, especially in Banua Baru Village, Wonomulyo District, Polewali Mandar Regency. This study aims to analyze the role of agricultural technology in increasing rice productivity, identify obstacles faced by farmers, and formulate strategic recommendations. This research uses a descriptive qualitative approach involving four farmers as informants. Data were collected through interviews, field observations, and document analysis. The findings show that the adoption of technologies such as superior rice varieties, the legowo planting system, and agriculture machinery (tractors, water pumps, combine harvesters) has increased rice yields by 25-30% and reduced production costs by up 15%. However, farmers still face barriers such as high initial investment, rising fuel prices, and limited access to technical training. This study recommends expanding subsidies for equipment, strengthening agriculture extension services, and improving irrigation infrastructure to optimize the use of agriculture technology in rural areas.